2007
DOI: 10.1002/jmv.20803
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating rotavirus vaccines in Brazil: Detection and molecular characterization of emerging rotavirus serotypes G8 and G9 among children with diarrhoea in Recife, Brazil

Abstract: In 2006, Brazil will initiate universal immunization of its 4-million infants with a live attenuated serotype G1P[8] human rotavirus vaccine. In anticipation of the national immunization program, this study was undertaken to characterize rotavirus strains circulating among children in Recife, one of the largest cities in the northeast region of Brazil. Group A rotaviruses were detected in 102 (35%) of 290 faecal specimens collected from children under 5 years of age who presented with acute diarrhoea during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
3
25
0
3
Order By: Relevance
“…9 Very recent studies carried out in Brazil revealed the emergence and predominance of genotype G9 in that country just before the introduction of universal vaccination against RV-A. [10][11][12][13][14][15][16] Currently, 6 different phylogenetic lineages and 11 sublineages within G9 RV-A have been described based on the genetic variability of the VP7 gene. 17 In the same way, sequence and phylogenetic analysis of the VP4 gene has demonstrated genetic diversity within the P [8] genotype, and four lineages have been described.…”
Section: Introductionmentioning
confidence: 99%
“…9 Very recent studies carried out in Brazil revealed the emergence and predominance of genotype G9 in that country just before the introduction of universal vaccination against RV-A. [10][11][12][13][14][15][16] Currently, 6 different phylogenetic lineages and 11 sublineages within G9 RV-A have been described based on the genetic variability of the VP7 gene. 17 In the same way, sequence and phylogenetic analysis of the VP4 gene has demonstrated genetic diversity within the P [8] genotype, and four lineages have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The first period included 653 RV-A-positive samples that were collected from 1982-1995; these cases were reported in 15 papers in our literature review (Linhares et al 1988, Stewien et al 1994, Gusmão et al 1995, Leite et al 1996, Mascarenhas et al 1998, Cardoso et al 2000, 2001, Carmona et al 2004. The second period included 1,839 RV-A-positive samples that were collected from 1996-2005; these cases were reported in 19 articles in our literature review (Santos et al 1998, 2005b, Araújo et al 2002, Rosa-e-Silva et al 2002, Souza et al 2003, Luz et al 2005, Carmona et al 2006, Carvalho-Costa et al 2006, 2009, Pietruchinski et al 2006, Andreasi et al 2007, Gouvea et al 2007, Montenegro et al 2007, Martini et al 2008, Domingues et al 2008, Ribeiro et al 2008. Altogether, during the pre-vaccination era, 2,492 RV-A-positive faecal samples were typed, either by use of monoclonal antibody or PCR assays.…”
mentioning
confidence: 99%
“…A global meta-analysis of 124 such studies showed G1 (65%) is the most predominant strain causing disease, followed by G2 (12%), G3 (3%), G4 (8.5%), and G9 (4%) [Santos and Hoshino, 2005]. Some areas have seen the emergence of less common strains such as G5 [Bok et al, 2001;Coluchi et al, 2002;Esona et al, 2004;Martini et al, 2008], G6 [Diwakarla et al, 2002;Martini et al, 2008], G8 [Steele and Ivanoff, 2003;Kirkwood et al, 2007;Montenegro et al, 2007], and G12 [Pietruchinski et al, 2006;Uchida et al, 2006;Kirkwood et al, 2007;Kheyami et al, 2008;Sharma et al, 2008].…”
Section: Introductionmentioning
confidence: 93%